Excessive tubulin polyglutamylation causes neurodegeneration and perturbs neuronal transport. (12th November 2018) - Magiera, Maria M; Bodakuntla, Satish; Žiak, Jakub; Lacomme, Sabrina; Marques Sousa, Patricia; Leboucher, Sophie; Hausrat, Torben J; Bosc, Christophe; Andrieux, Annie; Kneussel, Matthias; Landry, Marc; Calas, André; et al.
Abstract: Posttranslational modifications of tubulin are emerging regulators of microtubule functions. We have shown earlier that upregulated polyglutamylation is linked to rapid degeneration of Purkinje cells in mice with a mutation in the deglutamylating enzyme CCP1. How polyglutamylation leads to degeneration, whether it affects multiple neuron types, or which physiological processes it regulates in healthy neurons has remained unknown. Here, we demonstrate that excessive polyglutamylation induces neurodegeneration in a cell‐autonomous manner and can occur in many parts of the central nervous system. Degeneration of selected neurons in CCP1‐deficient mice can be fully rescued by simultaneous knockout of the counteracting polyglutamylase TTLL1. Excessive polyglutamylation reduces the efficiency of neuronal transport in cultured hippocampal neurons, suggesting that impaired cargo transport plays an important role in the observed degenerative phenotypes. We thus establish polyglutamylation as a cell‐autonomous mechanism for neurodegeneration that might be therapeutically accessible through manipulation of the enzymes that control this posttranslational modification. Synopsis: Excessive accumulation of polyglutamylation, a posttranslational modification of the neuronal microtubule cytoskeleton, leads to degeneration of a variety of neurons in mouse brains, and perturbs axonal transport. Removal of two deglutamylating enzymes in mouse brain leads to hyperglutamylation due to unopposed glutamylase activity in the entire brain. Hyperglutamylation can cause the degeneration of various neurons in the mouse brain. Concomitant deletion of the main brain glutamylase can prevent hyperglutamylation‐induced neurodegeneration in a cell‐autonomous manner. The microtubule‐severing enzyme spastin is not responsible for hyperglutamylation‐induced neurodegeneration. Axonal transport is perturbed in neurons with tubulin hyperglutamylation. Abstract : Neurodegeneration in mice lacking the tubulin‐deglutamylating enzyme CCP1 occurs in a cell‐autonomous manner and in various parts of the central nervous system.